Monolithic MWCNT-hyperelastic elastomer based electronic skin with ultra-high stretchability for human health monitoring - Pandey, Deepak; Singh, Rajan; Karmakar, Pratap; Das, Suranjan; Roy, Himadri; Sen, Soumen; Mandal, Soumen; Chanda, Nripen (Sensors and actuators. A. Physical., 2024)
This research reports developing and applying multi-walled carbon nanotube (MWCNT) embedded monolithic hyperelastic elastomeric sponge-based wearable electronic skin (e-skin) with ultra-high stretchability for human activity monitoring. The e-skin was fabricated by soaking conductive, MWCNT-based ink in a porous water-resistant sponge that was developed from an Ecoflex-NaCl combination followed by a salt dissolution technique. Material characterization studies revealed uniform distribution of MWCNTs inside the pores of the e-skin and adhesion of the MWCNTs to the sponge matrix. Electrical characterization results indicated a stretching span of 350% with minimal hysteresis and a fast dynamic response that was twice as high as reported compared to non-monolithic/ sandwiched MWCNT-elastomer structures. In addition, the sensor displayed excellent drift response, resolution of 1% strain at lower stretching limits, and repeatability of up to 10000 stretch-release cycles. The developed e-skin showed <1% response variations with temperature fluctuations within 50°C and was found to be water-resistant. The dynamic in-situ tensile testing results demonstrated the physics behind the piezoresistive properties of the fabricated e-skin. Finally, the e-skin worn over the finger, thoracic region, and epiglottis recognized finger bending angles, respiration rate, and distinguished English alphabets spoken by a subject, respectively. The hyperelastic e-skin hence finds applications in wearable devices and healthcare robotics. [Display omitted] •MWCNT-hyperelastic elastometer with high stretchability, low hysteresis and fast response as e-skin.•Physics behind change in resistance on stretching is found experimentally.•e-skin finds applications in human health monitoring.